Technical considerations for isolated limb perfusion: A consensus paper - Hayes, Andrew J.; Coker, David J.; Been, Lukas; Boecxstaens, Veerle WSM.; Bonvalot, Sylvie; De Cian, Franco; de la Cruz-Merino, Luis; Duarte, Carlos; Eggermont, Alexander; Farricha, Victor; Fiore, Marco; Grünhagen, Dirk; et al. (European journal of surgical oncology, 2024)
Background - Isolated limb perfusion (ILP) is a well-established surgical procedure for the administration of high dose chemotherapy to a limb for the treatment of advanced extremity malignancy. Although the technique of ILP was first described over 60 years ago, ILP is utilised in relatively few specialist centres, co-located with tertiary or quaternary cancer centres. The combination of high dose cytotoxic chemotherapy and the cytokine tumour necrosis factor alpha (TNFα), mandates leakage monitoring to prevent potentially serious systemic toxicity. Since the procedure is performed at relatively few specialist centres, an ILP working group was formed with the aim of producing technical consensus guidelines for the procedure to streamline practice and to provide guidance for new centres commencing the technique. - Methods - Between October 2021 and October 2023 a series of face to face online and hybrid meetings were held in which a modified Delphi process was used to develop a unified consensus document. After each meeting the document was modified and recirculated and then rediscussed at subsequent meeting until a greater than 90% consensus was achieved in all recommendations. - Results - The completed consensus document comprised 23 topics in which greater than 90% consensus was achieved, with 83% of recommendations having 100% consensus across all members of the working group. The consensus recommendations covered all areas of the surgical procedure including pre-operative assessment, drug dosing and administration, perfusion parameters, hyperthermia, leakage monitoring and theatre logistics, practical surgical strategies and also post-operative care, response evaluation and staff training. - Conclusion - We present the first joint expert-based consensus statement with respect to the technical aspects of ILP that can serve as a reference point for both existing and new centres in providing ILP.